Development of personal finance management application - Wong, Zhi Xuan (2024)
Efficient personal finance management is crucial for individuals to achieve their financial goals and secure their future. Existing approaches often face challenges such as inadequate expense tracking, unorganised transaction categorisation, and limited financial awareness. Inadequate expense tracking results from the manual recording of daily expenses, leading to incomplete records and overspending. Unorganized transaction categorization is time-consuming and prone to errors, hindering the analysis of spending patterns. Limited financial awareness arises from a lack of financial education and a focus on short-term needs. Several research on existing applications were conducted to identify the strengths and weaknesses of the applications. By addressing these challenges, this project aims to empower individuals with the tools and knowledge to manage their finances effectively. This project adopts the Rapid Application Development (RAD) methodology, emphasizing prototyping and rapid feedback. The project encompasses phases for determining requirements, user design, construction, and implementation. This iterative approach ensures the application meets user expectations and functions seamlessly. The proposed solution includes modules which are user authentication and profile management module, virtual wallet module, transaction tracking and categorization module, income or saving recording module, manual transaction input module, budget management and calculation module, goal-setting and tracking module, analytics module as well as receipt OCR module. Ultimately, this project led to better financial control and decision-making.